EasySLM‐STED: Stimulated emission depletion microscopy with aberration correction, extended field of view and multiple beam scanning. Issue 11 (31st July 2018) - Görlitz, Frederik; Guldbrand, Stina; Runcorn, Timothy H.; Murray, Robert T.; Jaso‐Tamame, Angel L.; Sinclair, Hugo G.; Martinez‐Perez, Enrique; Taylor, James R.; Neil, Mark A. A.; Dunsby, Christopher; French, Paul M. W.
Abstract : We demonstrate a simplified set‐up for STED microscopy with a straightforward alignment procedure that uses a single spatial light modulator (SLM) with collinear incident excitation and depletion beams to provide phase modulation of the beam profiles and correction of optical aberrations. We show that this approach can be used to extend the field of view for STED microscopy by correcting chromatic aberration that otherwise leads to walk‐off between the focused excitation and depletion beams. We further show how this arrangement can be adapted to increase the imaging speed through multibeam excitation and depletion. Fine adjustments to the alignment can be accomplished using the SLM only, conferring the potential for automation. Abstract : STED microscopy benefits from an SLM in various ways. This paper explores three possibilities; first the SLM is used in an easySTED‐like configuration to ensure coalignment between excitation and depletion beam, secondly the SLM is used to correct for aberrations in the excitation and depletion beam separately and finally the potential of parallelization is demonstrated. The improvements are tested on technical and biological samples, such as cells and Caenorhabditis elegans .